Fiscal responses to monetary policy: Insights from a survey among government officials - Andreas Dibiasi; Heiner Mikosch; Samad Sarferaz; Armin Steinbach (ETH Zurich, KOF Swiss Economic Institute, 2024)
This paper leverages a novel survey among German senior government officials to investigate fiscal responses to monetary policy shocks. Using randomized vignette treatments, we present officials with scenarios of increased government interest costs and analyze their expected fiscal adjustments. Our findings reveal that officials predominantly adjust fiscal policy by increasing debt and reducing spending, with tax increases being the least favored option. Moreover, they prefer adjusting multiple fiscal instruments simultaneously rather than changing a single instrument. In a back-of-the-envelope calculation, we compute the macroeconomic impact of a monetary policy shock under a mixed fiscal policy adjustment.
Keywords: D83; E62; E63; E52; 330; Fiscal policy; monetary policy; fiscal-monetary interaction; expectation formation; survey experiment